2010
DOI: 10.5114/aoms.2010.17091
|View full text |Cite
|
Sign up to set email alerts
|

The use of whey protein concentrate in management of chronic hepatitis C virus – a pilot study

Abstract: IntroductionWhey protein contains biologically active ingredients that can prevent and attenuate disease besides being nutritive. The aim of the study was to clarify the effects of oral administration of whey protein on viral load and host defence mechanisms, in particular, phagocytic function of neutrophils, selected immunomodulatory cytokines and serum inflammatory markers, in compensated chronic hepatitis C virus (HCV) patients.Material and methodsTwenty-seven HCV patients (20 males and 7 females) recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…However, in special cases such as diseases with significant liver injury (nonalcoholic steatohepatitis and chronic hepatitis) in which there is an inflammatory background established, WP supplementation have been demonstrated to be an interesting approach to decreasing the activity of liver enzymes and increasing glutathione concentration and total antioxidant capacity in plasma (Chitapanarux et al 2009). In a pilot study (Elattar et al 2010) of the chronic hepatitis C virus, WP supplementation in standard dose (twice per day for 8 weeks) was able to reduce inflammatory markers and liver enzyme (ALP and AST) activity. In this way, WP supplementation may play a beneficial role in treating liver injuries of some clinical populations.…”
Section: Discussionmentioning
confidence: 98%
“…However, in special cases such as diseases with significant liver injury (nonalcoholic steatohepatitis and chronic hepatitis) in which there is an inflammatory background established, WP supplementation have been demonstrated to be an interesting approach to decreasing the activity of liver enzymes and increasing glutathione concentration and total antioxidant capacity in plasma (Chitapanarux et al 2009). In a pilot study (Elattar et al 2010) of the chronic hepatitis C virus, WP supplementation in standard dose (twice per day for 8 weeks) was able to reduce inflammatory markers and liver enzyme (ALP and AST) activity. In this way, WP supplementation may play a beneficial role in treating liver injuries of some clinical populations.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, milk has antibacterial and antiviral properties (7). It was reported that milk components show antiviral activity against the HIV, HCMV and hepatitis C virus (HCV) (8)(9)(10). The Lactoferrin from the milk was reported to show antiviral activity and inhibition of intracellular HCV replication (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Oral supplementation of whey protein concentrate reduced the hepatitis C virus (HCV) burden in a clinical trial. Anti-inflammation, augmentation of hepatic and phagocytic functionality was discerned to be the underlying mechanism (Elattar et al 2010). Discovery of other prospective roles constitutes an exciting avenue.…”
Section: Emerging Ameliorative Rolesmentioning
confidence: 99%